Determination of Cobalt(II) Ion in Various Selected Alloys via Utilizing Continous Flow Injection Analysis ((CFIA) (Nagham-Four Sources of White Snow LED Arranged in Three Rows Corresponding to Three Detectors Analyzer) (NAG-4SX3-3D)) Analyzer at 0-180o Angle - Sadiq, Bakr; Shaker, Nagham (Iraqi Journal of Science, 2025)
The research study focuses on the efficient and accurate detection and determination of cobalt ions. The detection method involves the formation of brilliant green aggregates with calcium hexacyanoferrate in the presence of nitric acid. (Nagham-four sources of white snow light-emitting diodes arranged in three rows corresponding to three detectors) (The NAG-4SX3-3D Analyzer is an optical, chemical, electronic, and detection tool that receives a cumulative signal (no amplification is required). The total distance travelled is 760 mm with regard to YZ(mV) - tsec (dmm). It was selected for its precise calculation of the energy transducer profile. The linear range for measuring cobalt (II) ions is 0.05 to 20 mM. For concentrations of 5 and 10 mM, the relative standard deviation (RSD) for eight repeated intraday measurements is less than 0.36%. The calibration graph gradually dilutes the lowest concentration to determine the limit of detection (LOD) of 349.236 ng per analyte sample. The correlation coefficient (r) for the linear dynamic range is 0.9893, and the linearity is 97.80% (R2 %). The results of the proposed method were compared to the already-available UV-spectrophotometric technique at a wavelength of 510 nm and found to be comparable..